Traffic Control Systems of Nanosatellites in the Zone of the International Space Station. (2017) - Phylonin, Oleg; Belokonov, Igor; Nikolaev, Peter
Abstract: Ways and the automated devices for precision traffic control of nanosatellites (NS) in a zone of the Russian ISS segment are described. The complexity of management of these systems concerns the magnetic-induction system of separation of NS in the set directions specialized by NS supplied with ionic micromotors. The magnetic-induction system of separation contains a microprocessor system of management which allows high-precision start of the nanosatellite in the set azimuthal and zenith directions concerning the coordinate system connected with the ISS. The thrust vector of the ionic micromotors set on NS is regulated by means of a management system executed on microcontrollers. This combination of devices allows practically any trajectory to be set for NS concerned with the ISS.